Respuesta :
Answer:
5x + 2y + 5z
Step-by-step explanation:
Step 1: Write out expression
3x + 4y + 5z + 2x - 2y
Step 2: Combine like terms (x)
5x + 4y + 5z - 2y
Step 3: Combine like terms (y)
5x + 2y + 5z
The answer is 5x+2y+5z
That’s the answer because:
You have to combine like terms to simplify so do:
3x+2x=5x
4y+-2y=2y
5z is the only z variable
So you get
5x+2y+5z
That’s the answer because:
You have to combine like terms to simplify so do:
3x+2x=5x
4y+-2y=2y
5z is the only z variable
So you get
5x+2y+5z